1845 Ga. Laws 832 - (:unkn) unknown (My University, 1833)
Art. I, Sec. I, Pt. 41: Prohibition for "any free person of colour" to own, use, or carry any firearms.
Keywords: ENSLAVED PERSONS & OTHER MINORITIES